CHATGPT AS A SOCRATIC ASSISTANT: DEVELOPING STUDENTS’ REFLECTIVE AND CRITICAL THINKING - Wedsha Appadoo-Ramsamy (PUPIL: International Journal of Teaching, Education and Learning, 2025)
The introduction of ChatGPT and its use in the education sector has received varying responses. Termed as ‘apocalyptic’, ChatGPT presents an ethical dilemma with the possibility of leading students towards plagiarism, lack of criticality and passivity. However, if used properly, this tool, similar to other technological pedagogical tools that have initially been feared or criticised, may contribute to the development of STEM skills such as critical analysis, communication, independent thinking and reflection. Within this perspective and building on the principles of the Socratic Method with an emphasis on critical thinking, intellectual engagement and reflection, this paper explores the use of ChatGPT as a Socratic assistant. ChatGPT is, therefore, presented as a collaborative tool that enriches the learning environment whereby students can develop their critical skills, question assumptions, develop intellectual curiosity through prompting and eventually produce reflective and critical responses. This research adopts a posthumanist innovative methodology where data is produced through the intra-action between the researcher (human) and ChatGPT (non-human). The chosen methodology reflects the entanglement of the human (students, teachers) and non-human (AI) in an educational space dominated by chatbots and other technological assistance. Through generated examples, this paper shows how ChatGPT can be integrated into teaching and learning contexts, fostering deeper inquiry and self-reflection aligning with the Socratic Method. This research contributes to discourses on AI and its ethical use in transforming teaching and learning through innovative methods and may assist teachers in the development of innovative teaching practices assisted by AI.